Efficiency of secondary metabolites produced by Trichoderma spp against Fusarium oxysporum. - علي أبوالقاسم العاقل (The Libyan Journal of Science, 2024)
Trichoderma has been achieved great success as a biological control agent against most plant pathogens, including Fusarium spp. by several mechanisms, the most important of which is the production of secondary bioactive metabolites. Trichoderma spp. were isolated from the area around the roots of the olive plant using Trichoderma selective medium. Eight isolates were obtained and evaluated for their ability to inhibit Fusarium oxysporum using the dual plate bioassay, the inverted plates, and the cellophane membrane methods on Potato dextrose agar. Through these tests, the isolation (T3) was selected based on its ability for inhibit F. oxysporum in all tests used in this study for further investigation using GC-MS. These metabolites were detected and identified using gas chromatography-mass spectrometry. The results showed that the metabolites resulting from Trichoderma extract on the potato dextrose broth medium contained 21 compounds and the main compound was Phenylethyl Alcohol. The findings of this study demonstrated the antagonistic effectiveness of these metabolites in inhibiting F. oxysporum, as assessed by the agar diffusion assay. Previous research has shown that various metabolic compounds influence significant antifungal and antibacterial properties against pathogens responsible for plant diseases, with some even being used in pharmaceutical applications.